Regulatory Effects of Plant Growth Regulators on the Flowering of Cymbidium ensifolium - Rong ZHOU; Qixin HE; Chuqiao LU (Guangdong nongye kexue, 2023)
【Objective】The process of flower bud differentiation and development of Cymbidium. ensufolium was elaborated, and plant growth regulators were utilized for the flower buds at different developmental stages to solve the problems of non-uniformity of flowering period and short ornamental period of C. ensufolium, with an aim to provide references for the realization of annual production of C. ensufolium.【Method】Taking C. ensufolium 'Xiao Tao Hong' as the material, the characteristics of flower bud differentiation and development were observed through dissection, and the effects of different concentrations of plant growth regulators such as 6-BA, GA3, NAA, CH4N2O, and 3% gibberellic acid EC on flowering traits including inflorescence ratio, number of flowers, and diameter of flower in each flowering stage of C. ensufolium were investigated. In addition, silver thiosulfate (STS) was sprayed during the period of boll to analyze its effect on the duration of flower opening of C. ensufolium.【Result】The whole process of flower differentiation and development takes 30 days from the beginning of differentiation to the opening of flowers, which can be divided into six periods: Pre-differentiation, early differentiation, rapid development of flower buds, elongation of flower pedicels, periods of boll and flowering. Flower buds in different developmental periods react to plant growth regulators differently, and the combination of plant growth regulators sprayed before flower bud differentiation can advance the flowering period of C. ensufolium by one month, of which 200 mg/L 6-BA + 75 mg/L NAA + 10 mg/L CH4N2O + 50 mg/L 3% gibberellic acid EC has the optimal effect, with the flowering period being advanced by 33.03 d. The plant growth regulators sprayed at the rapid development of flower buds can advance the flowering period of C. ensufolium by about one week, among which 150 mg/L 6-BA + 75 mg/L GA3+ 50 mg/L NAA + 10 mg/L CH4N2O showing the best effect, which can advance the flowering period of C. ensufolium by 8.30 d. The spraying of 100 μmol/L STS during the period of boll of C. ensufolium can prolong the flowering period of single flower of C. ensufolium by 3.83 d.【Conclusion】C. ensufolium at different growth and development periods have their special needs and responses to the formation of flowers, and appropriate concentration of plant growth regulators can effectively regulate the flowering period of C. ensufolium, facilitating C. ensufolium flower to advance or prolong the flowering period.